Comprehensive Analysis of Buck Mode Frozen Leg Operation for Three-Phase Dual Active Bridge Converters - Wang, Cun; Bauman, Jennifer (IEEE transactions on power electronics, 2025)
The three-phase dual-active-bridge converter exhibits an inherent fault-tolerant capability for addressing open-circuit failures (OCFs). The frozen leg method is a notable fault-tolerant technique that mitigates OCFs without additional hardware. Upon OCF detection, this method deactivates the two switches in the faulty leg, enabling the converter to maintain operation at a reduced power level. However, all previous research on the frozen leg method assumes unity voltage gain. Yet, in practical applications, nonunity voltage gain, such as buck operation, is often unavoidable, wherein the voltage, current, and power characteristics significantly deviate from those at unity voltage gain. Thus, this article performs the first investigation of the more complex buck mode of frozen leg operation, and finds the operation must be categorized into three cases. The theoretical analysis derives the voltage, current, and power expressions for these cases, revealing significant deviations from those associated with unity voltage gain. Based on the derived current expressions, a detailed soft-switching analysis for the buck mode is also conducted. Furthermore, the theoretical maximum transferred power in buck mode under the frozen leg operation is proposed, and unique findings for power transfer at zero phase shift are examined. The theoretical analyses are validated through extensive experimental testing.